Near infrared broadband and visible upconversion emissions of erbium ions in oxyfluoride glasses for optical amplifier applications. (July 2020) - Kummara, Venkata Krishnaiah; Neelima, G.; Ravi, N.; Nanda Kumar Reddy, Nallabala; Satish Kumar Reddy, H.; Dwaraka Viswanath, C.S.; Lenine, D.; Surekha, G.; Padma Suvarna, R.; Yuvaraj, C.; Venkatramu, V.
Graphical abstract: Gain cross-section spectra of Er 3+ -doped PCfBfTiEr20 glass for the 4 I13/2  →  4 I15/2 transition. Highlights: Erbium (Er 3+ )-doped oxyfluoride (PCfBfTiEr) glasses have been synthesized. Judd-Ofelt (JO) phenomenological intensity parameters (Ω2, Ω4, Ω6 ) have been estimated. Intense eye-safe emission at 1534 nm has been obtained under 980 nm laser excitation. High emission cross-section and bandwidth product were obtained for PCfBfTiEr2.0 glass. Abstract: Optical and visible upconversion properties of erbium (Er 3+ )-doped oxyfluoro-titania-phosphate glasses (PCfBfTiEr) with the chemical composition of P2 O5 –CaF2 –BaF2 –TiO2 –Er2 O3 have been explored. An intense emission at 1.53 µm of Er 3+ -doped PCfBfTiEr1.0 glass was obtained upon excitation of 980 nm diode laser. In addition, green and red visible upconversion emissions were obtained upon the optical excitation of Er 3+ ions doped PCfBfTiEr glasses at 980 nm diode laser. Upconversion emission intensities and population densities of respective levels were tuned with the variation of Er 3+ ion concentration. Fluorescence decay curves of the 4 I13/2 level of PCfBfTiEr glasses were obtained upon 980 nm laser excitation in the pulsed mode and revealed a mono-exponential behavior. The stimulated emission cross-section ( σ em ), full width at half maximum (FWHM) and gain bandwidth product ( σ em  × FWHM) were found to be 9.3 × 10 −21  cm 2, 95.61 nm and 889.2 cm −2 nm for PCfBfTiEr2.0 glass, respectively. These results recommend that the Er 3+ ions doped PCfBfTiEr glasses may possibly be worthy for the laser and optical amplification applications at 1.53 µm.